Synthesis and Characterization of a Highly Ordered Mesoporous Bio-glass - Xuan Vuong, Bui; My Thanh, Ngo Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 1, 2020)
A highly ordered mesoporous bio-glass has been successfully prepared by the sol-gel method, in which copolymer pluronic P123 was used as a structure-creating template. The obtained material has the mesoporous structure with the high value of specific surface area (395.6 m 2 /g) and the 2D hexagonal pore architecture with the pore sizes from 5.5 to 7 nm. The ‘‘in vitro’’ experiment was effectuated by soaking the bio-glass powder in the simulated body fluid (SBF). The obtained results confirmed the bioactivity of the synthetic biomaterial through the quick formation of a hydroxyapatite layer after 1 day of immersion. Keywords : Bio-glass, pore size, mesoporous, bioactivity, ‘‘in vitro’’.